The First Imported Case Infected with Chikungunya Virus in Korea - Hwang, Jeong-Hwan (Infect Chemother, 2015)
Chikungunya is caused by an arbovirus transmitted by Aedes mosquito vector. With the increase of habitat of mosquito by global warming and frequent international travel and interchange, chikungunya reemerged and showed global distribution recently. Until now there has not been reported any case infected with chikungunya virus in Korea. A 23-year-old man has been the Republic of the Philippines for 1 week, and visited our emergency center due to fever and back pain. Chikungunya viral infection was diagnosed by specific IgM for chickungunya virus by enzyme-linked immunosorbent assayin Korea Centers for Disease Control and Prevention. His clinical course was self limited. We introduce the first imported case infected with chikungunya virus in Korea.